Vestibular Loss in Older Adults Is Associated with Impaired Spatial Navigation: Data from the Triangle Completion Task - Xie, Yanjun; Bigelow, Robin T.; Frankenthaler, Scott F.; Studenski, Stephanie A.; Moffat, Scott D.; Agrawal, Yuri (Frontiers in Neurology, 2017)
Background: Vestibular inputs have been shown to play a critical role in spatial navigation. In this study, we sought to evaluate whether vestibular loss due to aging contributes to impaired spatial navigation as measured by the Triangle Completion Task (TCT). Materials and methods: We recruited three types of participants: young controls <55 years of age, older controls ≥55 years of age, and older patients from a Neurotology Clinic with evidence of vestibular physiologic impairment but who did not have any known vestibular disorder. We performed the cervical vestibular myogenic evoked potential (cVEMP) to evaluate saccular function and video head impulse testing to quantify horizontal semicircular canal vestibulo-ocular reflex (VOR) gain. To assess spatial navigation ability, we administered the TCT, in which participants were conveyed along two segments of a pre-drawn triangular path and instructed to complete the final segment independently. We measured the angle (degrees) and distance (cm) of deviation from the correct trajectory. We evaluated the influence of vestibular inputs on TCT performance. Results: Forty-eight adults participated in the study (mean age: 62.0 years; 52.1% females), including 9 young controls, 15 older controls, and 24 clinic patients. Clinic patients had the greatest distance of deviation (67.7cm), followed by older controls (45.4cm), then young controls (27.8cm; p<0.01). Similarly, clinic patients had greater rotational angles (22.1 degree) compared to older (13.3 degree) and younger controls (12.4 degree; p<0.01). Following multivariate linear regression adjusting for demographic variables, loss of otolith function was associated with an 18.2cm increase in distance of deviation (95% CI: 15.2-47.4) and a 9.2 degree increase in rotational angle (95% CI: 3.0-15.5). Abnormal semicircular canal function was associated with a 26.0cm increase in distance of deviation (95% CI: 0.2-51.8) and a 10.8 degree increase in rotational angle (95% CI: 3.0-15.5). Participants with both otolith and canal abnormalities had a larger distance error (β=25.3, 95% CI: 6.2-44.4) and angle of deviation (β=18.1, 95% CI: 10.1, 26.2) than with either condition alone. Conclusion: Vestibular loss in older adults was associated with poorer performance on a dynamic spatial navigation task relative to old and young controls.